Quantitative Gait Analysis Of an Amputee Using Inertial Measurement Unit: A Case Study (Journal of Medical Device Technology, 2025)
This study presents a quantitative evaluation of lower limb joint motion using inertial measurement units (IMUs) for gait analysis. IMU sensors were attached to six lower limb segments of thirty-two healthy participants to capture knee and ankle kinematics during one gait cycle. A Butterworth filter was selected as the optimal preprocessing method to reduce noise and enhance signal clarity. The joint angles obtained from IMUs were compared with those from the Kinovea motion analysis system, with synchronization performed on a single gait cycle for each subject. Agreement between both systems was examined using the intraclass correlation coefficient (ICC), yielding values of 0.822 (right knee), 0.881 (right ankle), 0.797 (left knee), and 0.773 (left ankle), indicating moderate to excellent consistency. A case study involving an amputee further highlighted reduced motion range and gait asymmetry in the prosthetic limb, particularly during the swing phase. These findings suggest that IMUs provide a practical and cost-effective alternative for gait assessment in non-laboratory environments.
Keywords: gait analysis; inertial measurement unit; intraclass correlation coefficient; motion analysis comparison